EVALUATION OF SPECTRUM OF NON-TRAUMATIC ACUTE ABDOMINAL PAIN USING MULTIDETECTOR COMPUTED TOMOGRAPHY AND UNDERSTANDING ITS IMPORTANCE - Dr. S. SOWMYA, Dr. KANISHKA S PATIL, Dr. SHRUTHI MEDAM (South Eastern European Journal of Public Health, 2025)
Background: Acute abdominal pain is a common clinical presentation with a broad differential diagnosis. Non-traumatic acute abdominal pain (NTAAP) can result from various gastrointestinal, vascular, and infectious conditions. Multidetector computed tomography (MDCT) has emerged as a critical imaging modality for evaluating NTAAP, providing rapid and accurate diagnosis. Objective: To evaluate the spectrum of NTAAP using MDCT and assess its diagnostic accuracy, advantages, and limitations. Methods: A prospective study was conducted over one year with 100 patients presenting with acute abdominal pain at a tertiary care center. MDCT was performed on all patients to identify the underlying cause of pain. The diagnoses were confirmed through clinical evaluation, laboratory tests, and, when necessary, surgical intervention. Results: MDCT successfully identified a wide range of conditions, including appendicitis (30%), diverticulitis (20%), cholecystitis (15%), and mesenteric ischemia (10%). Additionally, it detected rare but critical conditions such as bowel perforations (5%) and abdominal aortic aneurysms (5%). The diagnostic accuracy of MDCT was 95%, with a high sensitivity for detecting abdominal emergencies. Conclusion: MDCT is an effective and reliable imaging tool for diagnosing NTAAP. It offers high diagnostic accuracy, rapid results, and comprehensive assessment of abdominal pathologies, making it a valuable modality in emergency settings. Despite concerns about radiation exposure and cost, its benefits outweigh the limitations, making MDCT an essential part of acute abdominal pain management.